If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(-x)-4+4x=x+5
We simplify the equation to the form, which is simple to understand
2(-x)-4+4x=x+5
Reorder the terms in parentheses
+(-2x)-4+4x=x+5
Remove unnecessary parentheses
-2x-4+4x=+x+5
We move all terms containing x to the left and all other terms to the right.
-2x+4x-1x=+5+4
We simplify left and right side of the equation.
+1x=+9
We divide both sides of the equation by 1 to get x.
x=9
| 13+3x=5x-5 | | 9x+4x=2x+3 | | 13-(4-k)=5k+10-7 | | 37-X=14 | | 48-6x=4x-2 | | 8-g= | | X+150=.75(x+150) | | 3(4x-9)+12=9 | | 5t-7=5t | | 2a+14=-2(-a-3) | | -m-9=15 | | -I-17I= | | 3d-15=3(5+d) | | 11x+2x-9=24 | | 3(4x-9)12=9 | | -2(2a-7)=14-4a | | 3x+8x=9 | | 4x^2+25=7 | | 4a+45+4a+45=31a-2 | | 2x+6+5x=20 | | -7+2x+3=3x+5+2x | | -3+b(x+4)=47 | | 3p-p-5p=-3p-6 | | 7y-6x=72 | | 10+2b=76.50 | | -3(y-2)=6-3y | | 9x-6x+4=-20 | | Y=4cos(6x) | | 56+28x= | | 16-4b=2(8-2b) | | 6*6-(7+5)= | | 3x^2+5x=11 |